THE RELATIONSHIP BETWEEN ACADEMIC BURNOUT AND SOCIAL MEDIA ADDICTION AMONG COLLEGE STUDENTS AT UNIVERSITAS NEGERI PADANG IN WRITING UNDERGRADUATE THESES - Tiara Naffisa; Free Dirga Dwatra (Causalita, 2024)
When college students experience burnout, depression, and other negative emotions, they tend to be very active in social media to mask and escape the pain from their personal issues while seeking a sense of achievement and self-worth. The purpose of this study is to examine the relationship between academic burnout and social media addiction among undergraduate students working on their final projects at Universitas Negeri Padang. The methodology used is a quantitative approach with a survey method. A total of 102 final-year students from 9 faculties at Universitas Negeri Padang participated in this study. Data collection utilized two measurement tools: Skala Pengukuran Burnout Mahasiswa Dalam Penyelesaian Skripsi and Bergen Social Media Addiction Scale (BSMAS), which were adapted and tested according to the research objectives. Hypothesis testing was conducted using SPSS 26.0. According to Spearman's rho analysis, a correlation coefficient of 0.381 was obtained, and the Sig. (2-tailed) value was 0.000 (ρ<0.05), indicating a positive correlation between the two variables among participants.